2007
DOI: 10.1177/0898010107301618
|View full text |Cite
|
Sign up to set email alerts
|

Breast Biopsy and Distress

Abstract: Reiki, when administered in the naturalistic setting of a complementary therapy office, did not suggest evidence of efficacy. An intervention offered within the bounds of the conventional care setting may be more feasible for addressing BB distress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 35 publications
1
22
0
2
Order By: Relevance
“…The differences showen between and within subjects suggest that Reiki intervention in breast cancer patients the day before the surgical procedure is an effective practice in improving the general patients' wellbeing. Not surprising our results are in line with past literature, that found similar results in cancer patients (34)(35)(36), also in the same phase of cancer care trajectory (surgical phase) (37,38).…”
Section: Discussionsupporting
confidence: 93%
“…The differences showen between and within subjects suggest that Reiki intervention in breast cancer patients the day before the surgical procedure is an effective practice in improving the general patients' wellbeing. Not surprising our results are in line with past literature, that found similar results in cancer patients (34)(35)(36), also in the same phase of cancer care trajectory (surgical phase) (37,38).…”
Section: Discussionsupporting
confidence: 93%
“…Reiki: Two small studies examining the effects of Reiki revealed no change in anxiety (Birocco et al, 2012;Potter, 2007). However, Tsang, Carlson, and Olson (2007) conducted a pilot study administering Reiki to women with various types and stages of cancer and reported a significant reduction in anxiety.…”
Section: Implications For Practicementioning
confidence: 94%
“…O terapeuta desbloqueia a energia no corpo, promovendo cura física e equilíbrio emocional, mental e espiritual. O TC irá restaurar a harmonia e o equilíbrio do sistema de energia da pessoa para ajudá-la na "autopoiese" (POST-WHITE et al, 2003).…”
Section: Introductionunclassified
“…O estresse-ansiedade é caracterizado por um estado de tensão psicossomática que pode ser trabalhado através das técnicas de imposição de mãos por estas produzirem relaxamento e, diferente de fármacos, praticamente sem registros de contra indicação com baixo custo de aplicação (PETERS, 1999).…”
Section: Introductionunclassified